2019
DOI: 10.1091/mbc.e18-09-0605
|View full text |Cite
|
Sign up to set email alerts
|

Robust and stable transcriptional repression inGiardiausing CRISPRi

Abstract: Giardia lamblia is a binucleate protistan parasite causing significant diarrheal disease worldwide. An inability to target Cas9 to both nuclei, combined with the lack of nonhomologous end joining and markers for positive selection, has stalled the adaptation of CRISPR/Cas9-mediated genetic tools for this widespread parasite. CRISPR interference (CRISPRi) is a modification of the CRISPR/Cas9 system that directs catalytically inactive Cas9 (dCas9) to target loci for stable transcriptional repression. Using a Gia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
113
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(120 citation statements)
references
References 71 publications
7
113
0
Order By: Relevance
“…To assess the contributions of kinesin-13 mediated disassembly to the maintenance of the lengths of all four flagellar pairs, we quantified all flagellar lengths in the CRISPRi-mediated kinesin-13 knockdown (K13kd) strain (Figure 6A, 6B). Using this K13kd strain, we have previously shown that caudal flagellar length increases (McInally et al, 2019). Here we extend this prior work to show that all flagellar pairs have steady-state length increases when kinesin-13 expression is inhibited by ∼60% (Figure 6A, 6B) (McInally et al, 2019), consistent with overexpression of a dominant negative rigor kinesin-13 mutant (Dawson et al, 2007).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…To assess the contributions of kinesin-13 mediated disassembly to the maintenance of the lengths of all four flagellar pairs, we quantified all flagellar lengths in the CRISPRi-mediated kinesin-13 knockdown (K13kd) strain (Figure 6A, 6B). Using this K13kd strain, we have previously shown that caudal flagellar length increases (McInally et al, 2019). Here we extend this prior work to show that all flagellar pairs have steady-state length increases when kinesin-13 expression is inhibited by ∼60% (Figure 6A, 6B) (McInally et al, 2019), consistent with overexpression of a dominant negative rigor kinesin-13 mutant (Dawson et al, 2007).…”
Section: Resultsmentioning
confidence: 96%
“…Using this K13kd strain, we have previously shown that caudal flagellar length increases (McInally et al, 2019). Here we extend this prior work to show that all flagellar pairs have steady-state length increases when kinesin-13 expression is inhibited by ∼60% (Figure 6A, 6B) (McInally et al, 2019), consistent with overexpression of a dominant negative rigor kinesin-13 mutant (Dawson et al, 2007). Compared to non-specific gRNA controls, the anterior flagella length in the K13kd strain is increased an average of 1.1±0.04 µm, the posteriolateral by 0.9±0.03 µm, the caudal by 3.1±0.18 µm, and the ventral by 1.6±0.06 µm (Figure 6H).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations